The potential for bacteria from carbon-limited deep terrestrial environments to participate in chlorine cycling. Issue 6 (3rd May 2022) - Bhattarai, Susma; Temme, Hanna; Jain, Abhiney; Badalamenti, Jonathan P; Gralnick, Jeffrey A; Novak, Paige J
Abstract: Bacteria capable of dehalogenation via reductive or hydrolytic pathways are ubiquitous. Little is known, however, about the prevalence of bacterial dechlorination in deep terrestrial environments with a limited carbon supply. In this study we analyzed published genomes from three deep terrestrial subsurface sites: a deep aquifer in Western Siberia, the Sanford Underground Research Facility in South Dakota, USA, and the Soudan Underground Iron Mine (SUIM) in Minnesota, USA to determine if there was evidence to suggest that microbial dehalogenation was possible in these environments. Diverse dehalogenase genes were present in all analyzed metagenomes, with reductive dehalogenase and haloalkane dehalogenase genes the most common. Taxonomic analysis of both hydrolytic and reductive dehalogenase genes was performed to explore their affiliation; this analysis indicated that at the SUIM site, hydrolytic dehalogenase genes were taxonomically affiliated with Marinobacter species. Because of this affiliation, experiments were also performed with Marinobacter subterrani strain JG233 ('JG233'), an organism containing three predicted hydrolytic dehalogenase genes and isolated from the SUIM site, to determine whether hydrolytic dehalogenation was an active process and involved in growth on a chlorocarboxylic acid. Presence of these genes in genome appears to be functional, as JG233 was capable of chloroacetate dechlorination with simultaneous chloride release. Stable isotope experiments combined with confocal Raman microspectroscopy demonstrated that JG233 incorporated carbon from 13 C-chloroacetate into its biomass. These experiments suggest that organisms present in these extreme and often low-carbon environments are capable of reductive and hydrolytic dechlorination and, based on laboratory experiments, may use this capability as a competitive advantage by utilizing chlorinated organic compounds for growth, either directly or after dechlorination. Abstract : Presence of dehalogenation genes and dechlorination by bacterial isolates from nutrient limited environment suggests that dechlorination might be one part of a microbial strategy to survive in those deep subsurface environments which could also have implications for remediation in nutrient limited condition.